Fenitization at the Lovozero Alkaline Massif, NW Russia: Composition and Evolution of Fluids - Olga D. Mokrushina; Julia A. Mikhailova; Yakov A. Pakhomovsky (Geosciences, 2023)
The 360–370 Ma old Lovozero massif (NW Russia) is a layered nepheline syenitic-foidolitic pluton. Despite its huge size (650 km2), the massif is surrounded by a narrow fenite aureole, and the most intensive fenitization is associated with pegmatites and hydrothermal veins that have intruded into the wall rocks. We studied petrography, petrochemistry, mineralogy and fluid inclusions along a profile crossing the direct contact of the Lovozero massif with country Archean gneiss. We found that the fluid responsible for fenitization was a heterogeneous mixture of two coexisting phases, an aqueous fluid with salinity 8.6–15.1 eq. wt.% NaCl and a methane fluid. The coexistence of these two fluids indicates immiscibility conditions at (or below) CH4–H2O solvus. The aqueous fluid affected both the endocontact alkaline rocks and country gneiss. In the endocontact, intense autometasomatic alterations of the early crystallized minerals occurred, for example, the natrolitization of nepheline and sodalite. Besides, the aqueous fluid transported Na2O, K2O, as well as P2O5, TiO2, H2O, F, Cl and S into the exocontact. These components were precipitated in the immediate vicinity of the massif contact, and the salinity of the aqueous fluid decreased to 0.53–3.06 eq. wt.% NaCl. We assume that there are two reasons for a narrow fenite aureole in the Lovozero massif: intense autometasomatic alterations and a decrease in the permeability of country rocks due to fluid immiscibility.